Ayat-Ayat Penciptaan Manusia (Studi Saintifik) - Wahyuni, Seri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Based on the background of the problem, the formulation of the problem in this research is how “Muhammad Abduh’s perspective on the verses of human creation scientific study). There are many arguments from commen tatoes and other science figures about the creation of man. Some say that humans were created similar to apes and some say that humans were created from a gushing drop of water (a drop of semen). However, Muhammad Abduh argues that humans were created from gushing water (a drop of semen), then his creation was perfected. There fore, the writer formulates the problem in this thesis is how “Muhammad Abduh’s perpective on the verses of human creation (scientifik studi). Based on the beckground and prevlous formulation, the author’s goal in this study is to study and examine how “Muhammad Abduh’s prespective in interpreting the creation of man (scientifik studi).The method used by the author in this research is to use a qualitative method (library research). Which examines scientifically to obtain valid data with the aim of being found, developed and proven in certain knowledge, research menhods also use the type of research in it. The data sources used in this research are primery and secondery data sources.The results of his study indicate that the creation of humans according to Muhammad Abduh in the interpretions of al-Manar and Juz’Amma, is that there are three kinds of human creation. Namely, the creation of the probhed Adam As from the ground, as described in QS. AL-An’am: 2. The second, creation of the probhet Isa As from dead diost and he is likened to the creation of the probhe Adam As contained in the QS. Al-Imran: 59. The rhird, creation of man (the children of Adam As) from a drof of gushing water (semen) contained in the QS. At-thariq: 5-7, QS. Abasa: 1, QS. Al-Alaq: 2, and perfected his creation in QS. Infithar: 7-8.